Study of The Influence of E-Procurement System on The Achievement of Project Progress Performance in Construction Projects Within The EPC Division - PT. PP Persero Tbk - Junaidi Heriyanto; M. Agung Wibowo; Bambang Purwanggono (Eduvest - Journal of Universal Studies, 2025)
Amid increasingly fierce competition in the construction industry due to the growing number of service providers and limited market share, achieving optimal cost performance, timely delivery, quality compliance, and zero workplace fatalities has become more challenging. To monitor project performance effectively, companies must establish Key Performance Indicators (KPIs) as benchmarks for project evaluation. One internal factor within PT. PP Persero Tbk is the centralized e-procurement system, which plays a crucial role, especially in EPC (Engineering, Procurement, and Construction) projects. Data from 2020–2022 indicates delays across centralized e-procurement processes in all projects, with procurement delayed in 7 out of 10 required steps: technical clarification, price negotiation, required negotiation evaluation documents, negotiation evaluation, objection period, contract draft review, and final contract wet signatures leading up to contract release. This highlights a suboptimal e-procurement progress performance. This study involved a survey comprising 61 variables related to the potential impact of e-procurement on progress performance, distributed among internal and external stakeholders. Validity and reliability tests were conducted prior to analysis using principal component analysis (PCA). A total of 43 respondents completed the survey. The results of the validity and reliability tests confirmed that all 61 variables were valid and reliable. PCA results identified 16 principal components, with 25 variables exhibiting positive loadings in Component 1, 18 variables in Component 2, and the remaining variables distributed across Components 3–6. The study indicates that focusing on Components 1–6 can serve as a priority framework for addressing variables to significantly improve e-procurement progress performance.